Nongenetic Determinants of Age at Menarche: A Systematic Review. (23rd June 2014) - Yermachenko, Anna; Dvornyk, Volodymyr
Abstract : Background . The acceleration of pubertal development is an important medical and social problem, as it may result in increased morbidity and mortality in later life. This systematic review summarizes relevant data about nongenetic factors, which contribute to age at menarche (AAM), and suggests those which may be the most important. Methods . The available literature from 1980 till July 2013 was searched using PubMed and Google Scholar databases. Finally, 154 papers were selected for the analysis. Results . Environmental factors, which may affect AAM, vary in populations of different ethnicity. The prenatal, infancy, and early childhood periods are the most susceptible to these factors. Body weight, high animal protein intake, family stressors (e.g., single parenting), and physical activity seem to influence AAM in most populations. Conclusions . The data about influence of nongenetic factors on AAM are still inconsistent. The factors affecting prenatal and early childhood growth seem to have a larger effect on further sexual maturation. Further studies are needed in order to validate the association between other environmental determinants and AAM in different ethnical groups.